Characteristics of tail pipe (Nitric oxide) and resuspended dust emissions from urban roads – A case study in Delhi city. (June 2020) - Dheeraj Alshetty, V.; Kuppili, Sudheer Kumar; Nagendra, S.M. Shiva; Ramadurai, Gitakrishnan; Sethi, Virendra; Kumar, Rakesh; Sharma, Niraj; Namdeo, Anil; Bell, Margaret; Goodman, Paul; Chatterton, Tim; Barnes, Jo; et al.
Abstract: Introduction: Personal exposure to elevated vehicle exhaust and non-exhaust emissions at urban roadside leads to carcinogenic health effects, respiratory illness and nervous system disorders. In this paper, an attempt has been made to investigate the exhaust and non-exhaust emissions emitted from selected roads in Delhi city. Methods: Based on the vehicular density per hour and speed, three categories of roads have been considered in the present study: (a) low density road (≤1000 vehicles/hour, V ≥ 10 m/s); (b) medium density road (>1000 vehicles/hour but ≤ 2000 vehicles/hour, V ≥ 7.5 m/s < 10 m/s); and (c) high density road (>2000 vehicles/hour, V < 7.5 m/s). At the selected roads, real-world exhaust emissions were measured using AVL DiTEST 1000 analyser. The silt load measurements were also carried out as per EPA AP-42 methodology at the selected roads. Results: Results indicated real-world NO exhaust emissions of 0.5 g/m 3 (2.03 g/km) on high-density roads and 0.23 g/m 3 (0.67 g/km) on low and medium density roads. These values were significantly higher than the Bharat Standard (BS) IV (0.25 g/km). The silt load on the different types of roads indicated 3, 25 and 44 g/m 2 -day dust deposition on, low, medium and high-density road, respectively. PM2.5 and PM10 emission rates were measured using US-EPA AP-42 methodology and were found to be least at low-density roads with values of 0.54 and 2.22 g/VKT (VKT -Vehicle Kilometer Travelled) respectively, and highest for high density roads with values of 12.40 and 51.25 g/VKT respectively. Conclusion: The present study reveals that both tailpipe (exhaust) and resuspend able road dust (non-exhaust) emissions contributes significantly and deteriorates local air quality. Although there exists emission standards, but there are no enforced regulations for non-exhaust emissions (resuspension of road dust). Hence, there is need to regulate non-exhaust emissions on urban roads. Highlights: Real time exhaust emission monitoring on different density roads along with dashboard monitoring. Characteristics of non-exhaust emission resuspendable road dust. Silt load and PM emission rates for low, moderate and high-density roads. Correlation between NO and vehicle speed at urban roads.